Konsep Kimia Pada Proses Pembuatan Tahu: Majalah Kimia Dengan Konten Etnokimia Sebagai Suplemen Pembelajaran Kimia SMA - Rahmawati, Rahmawati; Sari, Karmila; Al-Idrus, Syarifa Wahidah; Sofia, Baiq Fara Dwirani (FKIP University of Mataram, 2024)
This study aims to identify chemical concepts in tofu making and package them in the form of a magazine as a supplement to chemistry learning for high school. The development of a chemistry magazine uses a 4D model. The feasibility of ChemMag as a reading material is analyzed by validation tests and student and teacher responses. The identification results show that the chemical concepts in the tofu making process include: protein, fat, carbohydrates, organic acids, coagulation, colloids, and others. The results of the development are in the form of a chemistry magazine entitled ChemMag: chemical concepts in the tofu making process. The validation results show that the developed chemistry magazine has a validity level of 0.85 with a very valid category. The feasibility level is 84.79% and is categorized as very feasible. So it can be concluded that the ChemMag that has been designed is very feasible to be used as a supplement to chemistry learning in high school.